O eu íntimo e o eu social na poesia de Bueno de Rivera - Souza, Anderson Ibsen Lopes de (2009)
Bueno de Rivera’s poems present, on the compound of their characters, a high concern about the ontological factor, always searching for the human being’s description, as by the lyrical view, through intimate and subjective poetry, as on his everyday, exposing him as a being-with-the-others, immersed in society, besides presenting his anguish and piety with the human race’ suffering. This poetry combine with the postulates of Martin Heidegger’s ontological-existencialist philosophy, once it analyses the human being’s life from the point of view of the anguish from the conscience of the death and the quarrel about man, investigating the being-there – term that indicates the human’s existence, as well as with the being-with-the-others –, helping our understanding about the analyzed poet’s thoughts. Trying to comprehend the subjectivity on Rivera’s poems, we will analyze some of the Leitmotive chosen by him to develop his poetry, investigating the symbols and inquiring carefully the ideas. We believe that Bueno de Rivera’s poetry is a permanent searching for the unveiling of the human being from his own and the place in which he is inserted, in an inquisitor looking for everything that transforms him in man, that is, in a being single and social, at once.